Analisis Linear Programming Untuk Optimalisasi Keuntungan Menggunakan Metode Simpleks Pada UMKM Rambak DND Langgeng di Mojolaban Sukoharjo Linear Programming Analysis For Profit Optimization Using The Simplex Method On UMKM Rambak DND Langgeng in Mojolaba - Utama, Wahyu Putra; Widajanti, Erni (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2025)
Currently, many service and manufacturing companies compete to produce quality products to remain competitive in the market. Every company has the same goal, namely making a profit, producing useful products, and being able to compate. To achive this, good business management is needed by optimizing production to maximize profits. This optimization involves the efficient use of resources and production factors. This research was conducted at UMKM Rambak DnD Langgeng, a food industry, with the aim of: (1) to analyze the optimization of the amount of production and profit produced at UMKM Rambak DnD Langgeng, (2) to analyze the use of the Linier Programming (simplex) method to optimize the amount of production and the amount of profit at UMKM Rambak DnD Langgeng. Analyze using Linier Programming shows that optimal production occurs in plate rambak with 252,000 packs and a profit of IDR 504,000,000,00, while finger rambak (154,992 packs) and thin rambak (154,718 packs) have reached the optimal point.